Le biopic du sportif américain - Rémi Fontanel (Revue LISA)
This paper focuses on the specificities of biographical films dedicated to American sportsmen. Referring to more than fifty American films, it analyses the formal narrative and aesthetic elements that underlie the construction of sports heroes and celebrities, paying attention to the stories behind their public achievements. Golf, baseball, American football, athletics and boxing (to evoke only the five most popular sports within this subgenre) underpin sports adventures and intensely singular existential experiences. These cinematographic epics are steeped in such values as perseverance, sacrifice, belief in destiny, boldness, courage, etc., the man behind the athlete existing only in relation to the particular community he represents, challenges or dreams to fit in. Most of these biographical pictures are characterized by the figure of the sportsman represented as a committed figure, driven by a sense of revolt and fighting. On the other hand, they dramatize his personal path to success by highlighting the obstacles to overcome (racism, disease, accident, etc.), paving the way towards a progressive or populist symbol for the nation.